2018
DOI: 10.1038/s41591-018-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting G-quadruplex DNA as cognitive function therapy for ATR-X syndrome

Abstract: Alpha-thalassemia X-linked intellectual disability (ATR-X) syndrome is caused by mutations in ATRX, which encodes a chromatin-remodeling protein. Genome-wide analyses in mouse and human cells indicate that ATRX tends to bind to G-rich sequences with a high potential to form G-quadruplexes. Here, we report that Atrx mutation induces aberrant upregulation of Xlr3b expression in the mouse brain, an outcome associated with neuronal pathogenesis displayed by ATR-X model mice. We show that ATRX normally binds to G-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 57 publications
1
66
1
Order By: Relevance
“…The previously reported ATRX ΔE2 mice had impaired contextual fear memory, working memory, novel object recognition memory, and spatial memory in the Barnes maze 15,94 . Molecular analyses revealed decreased levels of CaMKII protein at synapses and increased expression of the Xlr3b gene, which is proposed to bind synaptic mRNAs and inhibit transport to dendritic spines 16 In conclusion, our study presents strong evidence that ATRX is required in forebrain excitatory neurons for spatial learning and long-term memory and regulation of genes required for efficient synaptic transmission.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The previously reported ATRX ΔE2 mice had impaired contextual fear memory, working memory, novel object recognition memory, and spatial memory in the Barnes maze 15,94 . Molecular analyses revealed decreased levels of CaMKII protein at synapses and increased expression of the Xlr3b gene, which is proposed to bind synaptic mRNAs and inhibit transport to dendritic spines 16 In conclusion, our study presents strong evidence that ATRX is required in forebrain excitatory neurons for spatial learning and long-term memory and regulation of genes required for efficient synaptic transmission.…”
Section: Discussionmentioning
confidence: 58%
“…These mice are viable and exhibit impaired novel object recognition memory, spatial memory in the Barnes maze, and contextual fear memory 15 . Some of the molecular defects identified in these mice included decreased activation of CaMKII and the AMPA receptor in the hippocampus as well as decreased spine density in the medial prefrontal cortex, and altered DNA methylation and increased expression of Xlr3b in neurons 16 . Our group also reported similar behavioural impairments in female mice exhibiting mosaic expression of ATRX in the central nervous system 17 .…”
Section: Introductionmentioning
confidence: 99%
“…5-ALA normalized Xlr3b expression presumably because its metabolites, protoporphyrin IX and hemin, bind to G4s interfering with the binding of ATAX and DNMTs. This appear to be an early indication of the potential that the drugs targeting IMs and G4s may have in neurological and psychiatric conditions 44 .…”
Section: Discussionmentioning
confidence: 95%
“…A recent study by Shioda and colleagues indicates that such effects not only occur in vivo but are relevant to the neuronal functions and potentially to neuroplasticity 44 . The researchers demonstrated that ATRX, a chromatin remodeling protein, acts by binding to G4 of the imprinted Xlr3b gene, regulating its expression.…”
Section: Cpc) Methylation Via Dnmt3amentioning
confidence: 99%
“…Transfection was performed using Lipofectamine 2000 (Invitrogen) transfection reagent according to the manufacturer's protocol. The primary cultures of neurons were established using previously described methods, with slight modifications (Shioda et al, 2018). Briefly, the raphe nucleus tissue was dissected from embryonic day 18 mice, and dissociated by trypsin treatment and trituration through a Pasteur pipette.…”
Section: Methodsmentioning
confidence: 99%